Super-cooling and thermochromic roof and exterior wall coatings
Patent Information
- Application Number
- JP2024549761
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-25
- Filing Date
- 2023-02-22
- Publication Date
- 2025-03-13
AI Technical Summary
【0031】 本発明において、フリットは、マルチスケールHRNPを含み、特殊なガラス質エナメルを生成する。フリットは、HRNPの融解温度より低い温度で焼成するため、得られるHRNP含浸ガラス質エナメルコーティングには、高い光放射率及び反射率比が維持される。ガラス質エナメルコーティングは、耐久性に優れ、その寿命は約40~50年で、塗料、エポキシ樹脂、及びポリエチレンエアロゲルなどの放射冷却に使用され得る他の屋根用及び外壁用コーティングの寿命を大幅に上回る。
Smart Images

Figure 2025506803000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of one or more inventions disclosed in U.S. Provisional Patent Application No. 63 / 313,860, entitled "ULTRA-COOL AND THERMOCHROMIC ROOF AND SIDING COATINGS," filed February 25, 2022. The benefit of the U.S. Provisional Patent Application pursuant to 35 U.S.C. § 119(e) is hereby claimed, and the aforementioned application is hereby incorporated by reference herein.
[0002] The present invention relates to roof and exterior wall coatings, and more particularly to supercooling and thermochromic roof and exterior wall coatings. [Background technology]
[0003] In developed countries, significant electrical energy is used to cool buildings through air conditioning systems. In less developed countries, the lack of cooling in buildings significantly impacts the health and well-being of many individuals and the productivity of workers. Passive cooling techniques have been developed to cool buildings without using energy, but developing passive cooling techniques that are reasonably cost-effective, effective, and durable remains a major challenge.
[0004] Radiative cooling is a type of passive cooling in which a building is cooled by the radiation of the building's emitted solar energy from its roof and exterior walls to the sky. Even during hours of direct sunlight, radiative cooling can allow the exterior surfaces of passively cooled roofs and exterior walls to reach temperatures lower than the surrounding air temperature.
[0005] The solar sky window is the frequency band of solar radiation at a given altitude on Earth. At sea level, most of the solar sky window ranges from ultraviolet (UV) at about 300 nm to infrared (IR) at about 2,500 nm, with most solar energy being in the IR range. A key challenge is to develop coatings for building roofs and exterior walls that provide advanced radiative cooling across the entire solar sky window from UV to IR at the height of the building. Within the solar sky window, the total solar radiation consists of 48% in the near infrared (NIR) spectrum, 45% in the visible spectral region, and 7% from UV radiation.
[0006] It should be noted that the terms optical emissivity and optical reflectivity used within this application refer to emissivity and reflectivity throughout the entire solar sky window, not just the visible spectrum. Emissivity is the ratio of the thermal radiation of a surface to the radiation of an ideal black body at the same temperature, this ratio ranges from 0 to 1, with an emissivity of 0 indicating that the material is a perfect reflector and an emissivity of 1 indicating that it is a perfect emitter. The solar reflectance ratio is the ratio between the solar energy totally reflected by a surface and the total incident solar energy. Important criteria for radiative cooling coatings are the emissivity and solar reflectance ratio within the frequency band of ground level solar radiation, as well as the cost, durability and toxicity of the coating.
[0007] A supercooled radiative cooling coating should have both a very high optical emissivity ratio and a very high optical reflectance ratio across the entire solar sky window. Various coatings, such as paints, epoxies, and polyethylene aerogels, have been proposed for supercooled radiative cooling of roofs and exterior walls, but their durability is limited.
[0008] In some geographic locations, solar radiation and ambient temperatures vary significantly from day to day and from season to season. Particularly in the summer and during the day, the location may be hotter due to solar radiation and may benefit from radiative cooling from roofs and exterior walls. On the other hand, particularly in the winter and at night, the location may be cooler and may benefit from radiative absorption from roofs and exterior walls. It is a challenge to provide roof and exterior wall coatings whose radiative cooling and radiative absorption properties change with temperature.
[0009] Vitreous enamel (also called porcelain enamel) is a very durable material. Its advantages include high resistance to weathering, abrasion, and chemicals, as well as mechanical hardness. The thickness of conventional vitreous enamel generally ranges from 0.3 mm to 1.3 mm. Vitreous enamel can be produced by fusing a powder called a frit, which is mainly composed of silica (silicon dioxide), and other materials to a substrate by firing at high temperatures of 730 °C to 870 °C.
[0010] Generally, frits are composed of various oxides, including adherent oxides, refractories, and fluxes. Adhesive oxides, such as cobalt oxide (CoO), nickel oxide (NiO), and copper(II) oxide (CuO), provide adhesion to the substrate surface. Refractories, such as silicon dioxide (SiO2) and aluminum oxide (Al2O3), are acidic glass-forming oxides that provide structural strength to the vitreous enamel, and they also increase viscosity and chemical resistance. Fluxes, such as boron oxide (B2O3), sodium oxide (Na2O), potassium oxide (K2O), lithium oxide (Li2O), and zinc oxide (ZnO), are alkaline oxides that react with the refractories and lower the softening temperature of the glass, aiding in the formation of the vitreous enamel matrix, and increasing surface hardness. Both refractories and fluxes also reduce the rate of expansion and reduce cracking.
[0011] All percentages given herein are by weight, with the percentages of the listed components of the frit being based on the total weight of the frit and the percentages of the listed components of the substrate being based on the weight of the substrate.
[0012] The frit composition will actually depend on the substrate surface and whether the enamel is a ground coat or cover coat on the substrate surface. For frits that do not contain opacifiers and coloring oxides, there are several acceptable frit compositions that are generally used in practice, as described below.
[0013] For a ground coat on steel sheet, the frit mixture can be 25% feldspar, 35% borax, 20% quartz, 6.5% soda ash, 4% sodium saltpeter, 7% fluorspar, 0.5% cobalt oxide, 0.5% nickel oxide, and 1.5% tin oxide, or, also for a ground coat on steel sheet, the frit mixture can be 20.4% feldspar, 35.8% borax, 17.7% quartz, 5.3% soda ash, 4.5% sodium saltpeter, 4.9% fluorspar, 6.5% barium carbonate, 2.4% sodium silicofluoride, 0.5% cobalt oxide, 0.5% nickel oxide, and 1.5% tin oxide.
[0014] For a steel cover coat, the frit mixture can be 27% feldspar, 25% borax, 24% quartz, 4.1% soda ash, 6% sodium nitrate, 4.4% fluorspar, 11% cryolite, and 6% antimony oxide, or, also for a steel cover coat, the frit mixture can be 22.8% feldspar, 23.1% borax, 21.1% quartz, 6.3% soda ash, 3% sodium saltpeter, 3.4% fluorspar, 10.1% cryolite, and 6.8% sodium antimonate, and 3.4% zinc oxide.
[0015] The substrate surfaces to which the vitreous enamel can be applied may be metals such as steel, galvanized iron, cast iron, aluminum, zinc, tin, copper, as well as mixtures of metals, and metal substrates with metal coatings.
[0016] Steels used for enameling generally contain less than 0.20% carbon, which reduces blistering of the enamel. Special steel substrate surfaces developed as substrates for vitreous enamel include decarbonized enameled steel (used for one-step enamel coating), void-free enameled steel (a moderately low carbon steel, but stronger), cold-rolled aluminized steel (a low carbon steel), and cold-rolled rimmed steel (a lower quality steel, which reduces the quality of the vitreous enamel).
[0017] Enamelled iron is a high-quality, nearly pure iron with a very low carbon content, but requires a two-stage enamel firing. Cast iron has a carbon content of at least 2.06%, generally 3.25% to 3.60%, and additional chemicals, including carbon, silicon, phosphorus, manganese, and sulfur, are generally added to promote enamelling.
[0018] Alternatively, the substrate surface may not be metal, but instead may be clay, pottery, earthenware, stoneware, terracotta, ceramic tile, brick, fiber cement, concrete, or stone such as slate. In these cases, the coating applied to the substrate surface is generally referred to as ceramic glazing. The composition of a standard ceramic glazing frit may vary considerably. An exemplary frit composition is 24.03% basalt, 14.68% sodium feldspar, 2.89% sodium carbonate (Na2CO3), 10.26% boric acid, 5.97% ZnO, 4.42% calcium carbonate (CaCO3), 14.43% zirconium (IV) silicate (ZrSiO4), 20.32% opalite, 2.80% barium sulfate (BaSO4), and 0.96% potassium nitrate (KNO3).
[0019] The production of vitreous enamel can be carried out in several stages, some of which are optional.
[0020] The substrate surface is typically first prepared by application of various substances such as a degreaser (for metal substrate surfaces), pickling (to etch the metal substrate surface and provide anchoring points for the vitreous enamel), pH neutralization, and rinsing, and may also include a pre-fire of a ground coat (also called an undercoat) to further promote adhesion to the substrate.
[0021] After such preparation of the substrate surface, the primary frit may be applied to the substrate surface by a variety of dry and wet techniques, each of which requires a specific frit composition. A dry application technique is electrostatic deposition, in which an organosilane capable of holding a charge encapsulates the dry frit, allowing electrostatic attachment to the substrate surface. A wet application technique is flow coating, in which a slurry of the frit is flowed over the surface of the substrate surface.
[0022] For a dry process cast iron cover enamel coat, the frit mixture can be 34.3% feldspar, 19.3% borax, 7.7% soda ash, 2.6% soda peter, 7.3% fluorspar, 3.4% cryolite, 9.2% zinc oxide, 8.1% minium, and 8.1% tin oxide.
[0023] For a wet process cast iron cover enamel coat, the frit mixture can be 23% feldspar, 24% borax, 12% quartz, 8% soda peter, 2% fluorspar, 6% cryolite, 10% barium carbonate, 4% sodium silicofluoride, 6% zinc oxide, 10% boric acid, and 8% antimony oxide.
[0024] After the frit is applied to the surface of the substrate, a primary firing is performed at a temperature of about 750° C. to 850° C. to fuse the frit to the substrate and form a primary coat.
[0025] The time and temperature of the primary firing depend on the substrate surface. Aluminum enamel is fired at 538°C-593°C for 10 minutes. Dry cast iron is fired at 816°C-927°C for 5 minutes. Wet cast iron is fired at 732°C-816°C for 10-20 minutes. Steel sheet ground coat is fired at 760°C-871°C for 1-4 minutes.
[0026] Following this first fire, which fuses the frit to the substrate, there may be subsequent fires in which additional frits are used to assemble layers of vitreous enamel of distinct composition over the primary coat. For example, a sheet steel ground coat is fired, followed by a sheet steel cover coat, which is fired at 816°C to 927°C for 1 to 3 minutes. Summary of the Invention [Means for solving the problem]
[0027] In the present invention, a vitreous enamel coating impregnated with highly reflective nanoparticles is applied to a substrate surface to provide high reflectance over the range of solar irradiance within a solar sky window. Highly reflective nanoparticles (HRNPs) have high melting points and reflectance, allowing them to be fired without significantly changing their reflectance.
[0028] In one embodiment, the HRNPs are selected from the group consisting of barium sulfate (BaSO), hexagonal boron nitride (h-BN), zirconium silicate (ZrSiO), titanium dioxide (TiO), calcium carbonate (CaCO), zinc sulfide (ZnS), silicon dioxide (SiO), magnesium oxide (MgO), yttrium orthoaluminate (AlO 12 Y3), calcium oxide (CaO), magnesium aluminate (Al2MgO4), and lanthanum aluminate (LaAlO3).
[0029] The reflectance of HRNPs depends on the particle size and chemistry of the particular mixture of nanoparticles. In an embodiment of the invention, the HRNPs are multi-scale with a distribution of particle sizes to provide high reflectance across the full range of solar radiation. For example, larger particle sizes provide IR reflectance and smaller particle sizes provide UV reflectance. The invention employs a selection of a distribution of HRNPs of multiple particle sizes, where the selection of HRNPs and their particle sizes is optimized to ensure a distribution of high reflectance across a range of solar radiation frequencies.
[0030] In one embodiment of the invention, the size range of the multi-scale HRNPs is continuous from smallest to largest, in other embodiments of the invention, the size range of the multi-scale HRNPs is discontinuous and the mixture of multi-scale HRNPs is formed from a mixture of two or more uniformly sized HRNPs.
[0031] In the present invention, the frit contains multi-scale HRNPs to produce a special vitreous enamel. The frit is fired below the melting temperature of the HRNPs, so that the resulting HRNP-impregnated vitreous enamel coating maintains a high optical emissivity and reflectance ratio. The vitreous enamel coating is highly durable, with a lifespan of approximately 40-50 years, significantly exceeding the lifespan of other roofing and exterior wall coatings that may be used for radiative cooling, such as paints, epoxies, and polyethylene aerogels.
[0032] Embodiments of the HRNP impregnated vitreous enamels of the present invention can be fired onto metal substrate surfaces including steel, galvanized iron, cast iron, aluminum, zinc, tin, copper, as well as onto mixtures of metals and even onto metal substrates with metal coatings.Embodiments of the HRNP impregnated vitreous enamels of the present invention can also be fired onto non-metallic roofing and exterior wall materials such as clay, terra cotta, ceramic tile, brick, fiber cement, concrete, and stone such as slate, as well as onto mixtures of these materials.
[0033] The vitreous enamel coating comprises one or more highly reflective multi-scale nanoparticles ranging from 2 to 40% of the total weight of the vitreous enamel coating, depending on the thickness of the coating. [Brief description of the drawings]
[0034] [Figure 1] 1 shows solar radiation on a roof with reflectance.
[0035] [Diagram 2] 1 shows a cross section of vitreous enamel containing highly reflective nanoparticles with multi-scale dispersed particle sizes.
[0036] [Diagram 3] 1 shows a flow chart of a method for applying an enamel coating to a substrate surface. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0037] The terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the present invention. As used herein, the singular forms "a", "an" and "the" are intended to include the plural as well as the singular, unless the context clearly indicates otherwise. It is further understood that as used herein, the terms "comprises" and "comprising" specify the presence of stated features, steps, operations, elements, and components, but do not exclude the presence or addition of one or more other features, steps, operations, elements, components, and groups thereof.
[0038] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by those skilled in the art to which this invention belongs. Terms as defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the relevant art and this disclosure, and should not be interpreted as idealized or overly formal unless expressly defined herein.
[0039] In describing the present invention, it should be understood that a number of techniques and steps are disclosed. Each of these has its own advantages, and each can also be used in conjunction with one or more, or in some cases all, of the other disclosed techniques. Thus, for the sake of clarity, this description refrains from unnecessarily repeating all possible combinations of the individual steps. Nevertheless, the specification and claims should be read with the understanding that such combinations are fully within the scope of the present invention and claims.
[0040] All percentages given herein are by weight, with the percentages given of the components of the frit being based on the total weight of the frit, and the percentages given of the components of the substrate being based on the weight of the substrate.
[0041] A novel type of vitreous enamel is discussed herein. In the following description, for purposes of explanation, numerous specific details are set forth in order to provide a thorough understanding of the invention. However, it will be apparent to one skilled in the art that the invention may be practiced without these specific details.
[0042] The present disclosure is to be considered as an exemplification of the invention and is not intended to limit the invention to the specific embodiments illustrated by the following drawings or description.
[0043] The present invention describes a novel type of vitreous enamel containing multi-scale highly reflective nanoparticles that can be fired onto many metal substrate surfaces, including steel, galvanized iron, cast iron, aluminum, zinc, tin, copper, as well as mixtures of metals and metal substrates with metal coatings. Additionally, the vitreous enamel can be fired onto many non-metallic roofing and exterior materials, such as clay, terracotta, ceramic tile, brick, fiber cement, concrete, and stone, such as slate, as well as mixtures of these materials.
[0044] Figure 1 illustrates solar radiation on a reflecting roof. Roof 1 preferably has a vitreous enamel coating 10 according to an embodiment of the present invention. Vitreous enamel coating 10 receives solar radiation 3 from the sun 2. The solar radiation is reflected 4 by the vitreous enamel coating 10.
[0045] Embodiments of the present invention employ highly reflective nanoparticles (HRNPs) that have a melting point high enough that the reflectivity of the HRNPs is not compromised during the firing process associated with applying a vitreous enamel coating to a substrate surface.
[0046] The HRNPs contained in the vitreous enamel coating preferably comprise a distribution of nanoparticle sizes that provide high reflectance over the entire range of solar radiation from IR to UV.
[0047] The nanoparticles used in the embodiments of the present invention are of a size less than 2000 nm. Often, nanoparticles of a particular size and composition have emission and reflection spectra limited to a limited frequency band. The embodiments of the present invention do not exclusively use nanoparticles of a single size. As used herein, the term "multi-scale nanoparticles" refers to a collection of nanoparticles where the nanoparticles have a distribution of sizes or nanoparticles of multiple sizes.
[0048] In one embodiment, the HRNPs are selected from the group consisting of barium sulfate (BaSO), hexagonal boron nitride (h-BN), zirconium silicate (ZrSiO), titanium dioxide (TiO), calcium carbonate (CaCO), zinc sulfide (ZnS), silicon dioxide (SiO), magnesium oxide (MgO), yttrium orthoaluminate (AlO 12 Y3), calcium oxide (CaO), magnesium aluminate (Al2MgO4), and lanthanum aluminate (LaAlO3).
[0049] The particle size distribution associated with exemplary HRNPs is shown below in Table 1. Figure 2 shows a cross section 10 of vitreous enamel containing highly reflective nanoparticles 5-8 of multiple scales of particle size distribution. [Table 1]
[0050] These materials are not considered hazardous under existing OSHA hazard communication regulations and are much less toxic than other nanoparticles, such as carbon nanotube nanoparticles.
[0051] In one embodiment, the one or more multi-scale HRNPs have a distribution of nanoparticles between 10 and 900 nm.
[0052] It should also be noted that multi-scale nanoparticles with a wide size distribution can provide a much broader frequency band spectrum in emission and reflectance. For example, a nanoparticle size distribution of barium sulfate (BaSO4) from 170 nm to 530 nm results in a phonon resonance at 9 μm, resulting in very high optical emissivity (~96%) and optical reflectance (~97.6%) within the full frequency band of the solar sky window of ground-level solar radiation. A nanoparticle size distribution of hexagonal boron nitride (h-BN) from 140 nm to 525 nm results in optical emissivity (~83%) and optical reflectance (~97.9%) within the full frequency band of the solar sky window of ground-level solar radiation. A nanoparticle size distribution of titanium dioxide (TiO2) from 140 nm to 600 nm results in optical emissivity (~92%) and optical reflectance (~95%) within the full frequency band of the solar sky window of ground-level solar radiation. A nanoparticle size distribution of zirconium silicate (ZrSiO4) between 160 nm and 550 nm provides optical emissivity (~95%) and optical reflectivity (~97%) within the full frequency band of the solar sky window for ground-level solar radiation.
[0053] In some embodiments, a thermochromic material is added. Thermochromic materials exhibit a phase change in optical properties with a change in temperature. Vanadium dioxide (VO2) is a thermochromic material that undergoes a phase change from transparent to IR below 68°C to reflective to IR above 68°C. Nanoparticles of vanadium dioxide provide particularly favorable thermochromic properties. The phase change temperature of vanadium dioxide can be lowered by doping with various materials including tungsten, magnesium, and molybdenum. For example, 1.9% tungsten lowers the phase change temperature to 29°C.
[0054] FIG. 3 shows a flow chart of a method for applying an enamel coating to a substrate surface.
[0055] The first step is to prepare the substrate surface (step 100). The substrate surface may be metal, such as steel, galvanized iron, cast iron, aluminum, zinc, tin, copper, as well as metal mixtures and metal substrates with metal coatings. Alternatively, the substrate surface may not be metal, but may instead be clay, pottery, earthenware, stoneware, terracotta, ceramic tile, brick, fiber cement, concrete, or stone, such as slate. Depending on the substrate surface, various substances are applied, such as degreasers (for metal substrate surfaces), pickling (to etch the metal substrate surface and provide anchoring points for the vitreous enamel), pH neutralization, and rinsing. A ground coat (also called an undercoat) may also be pre-fired to further promote adhesion to the substrate.
[0056] Next, the thickness of the coating on the substrate surface is determined, as well as whether the coating is a ground coat / undercoat, cover coat, or primary coating (step 102). A cover coat is a coat that cannot be applied directly to the substrate surface, but instead must be applied to a ground coat. A ground coat is the first coat that is applied directly to the substrate surface and promotes adhesion of subsequent coats. Some ground coats do not require additional coats.
[0057] The type of coat will determine the composition of the frit, the temperature of the first firing, and the temperature and need for any additional firings. In general, the type of coat does not dictate whether wet or dry techniques are used in applying the frit, although wet methods may include adding clay to the primary frit.
[0058] The thickness of the coating determines the percentage of nanoparticles added to the frit in the subsequent steps. Traditionally, vitreous enamel has a thickness of 0.3-1.33 mm, with an average thickness of 0.8 mm. In an embodiment of the invention, for an enamel coating thickness range of 0.3-1.33 mm, 5-15% nanoparticles are added to the frit.
[0059] As the thickness of the enamel coating increases, the percentage of nanoparticles in the frit decreases linearly: for example, for a thickness of 1.2 mm, 3.3–10% nanoparticles are required.
[0060] If the thickness of the enamel coating is decreased, the percentage of nanoparticles in the frit increases linearly, so for a thickness of 0.4 mm, the percentage of nanoparticles required is 10-30%.
[0061] The above thicknesses and percentages of multi-scale HRNPs can vary outside of the examples given above, in one embodiment, the vitreous enamel coating comprises 2-40% of one or more highly reflective multi-scale nanoparticles by total weight of the vitreous enamel coating.
[0062] A primary frit containing multiscale HRNPs is then prepared (step 104). It should be noted that nanoparticles of a single size are not used exclusively. Preferably, a size distribution of nanoparticles ranging from 170 to 530 nm is incorporated into the primary frit. The primary frit is prepared by melting various minerals in a furnace and then rapidly quenching the molten material to obtain granules, which are then dried.
[0063] In one embodiment, the frit is composed of various oxides, including adherent oxides, refractories, fluxes, opacifiers, colorants, and multi-scale HNRPs. Adhesive oxides, such as CoO, NiO, and CuO, provide adhesion to the substrate surface. Refractories, such as SiO2 and Al2O3, are acidic glass-forming oxides that provide structural strength to the vitreous enamel, and they also increase viscosity and chemical resistance. Fluxes, such as B2O3, Na2O, K2O, Li2O, and ZnO, are alkaline oxides that react with the refractories and lower the softening temperature of the glass, aiding in the formation of the vitreous enamel matrix. They also increase surface hardness. Both refractories and fluxes also reduce the expansion rate and reduce cracking. Opacifiers, such as ZIO2, Sb2O3, TiO3, and P2O5, can be added to create opacity (increased whiteness) and improve acid resistance.
[0064] The multi-scale HNRPs added to the frit are barium sulfate (BaSO4), hexagonal boron nitride (h-BN), zirconium silicate (ZrSiO4), titanium dioxide (TiO2), calcium carbonate (CaCO3), zinc sulfide (ZnS), silicon dioxide (SiO2), magnesium oxide (MgO), yttrium orthoaluminate (Al5O 12 The total percentage of multi-scale HNRP in the frit composition is 5-30% of the total weight of the vitreous enamel.
[0065] In one embodiment, the multi-scale HNRP is made of barium sulfate (BaSO), hexagonal boron nitride (h-BN), zirconium silicate (ZrSiO), titanium dioxide (TiO), calcium carbonate (CaCO), zinc sulfide (ZnS), silicon dioxide (SiO), magnesium oxide (MgO), yttrium orthoaluminate (AlO 12Y3), calcium oxide (CaO), magnesium aluminate (Al2MgO4), and lanthanum aluminate (LaAlO3).
[0066] In another embodiment, the multiscale HNRPs in the frit are two types of nanoparticles in relative proportions (%) that optimize the total reflectance on a solar sky window, the two types of nanoparticles being barium sulfate (BaSO4), hexagonal boron nitride (h-BN), zirconium silicate (ZrSiO4), titanium dioxide (TiO2), calcium carbonate (CaCO3), zinc sulfide (ZnS), silicon dioxide (SiO2), magnesium oxide (MgO), yttrium orthoaluminate (Al5O 12 Y3), calcium oxide (CaO), magnesium aluminate (Al2MgO4), and lanthanum aluminate (LaAlO3).
[0067] In a first example, where the substrate surface is a steel plate and the coat to be applied is a ground coat having a thickness of 0.8 mm, the frit includes 25% feldspar, 35% borax, 20% quartz, 6.5% soda ash, 4% soda peter, 7% fluorspar, 0.5% cobalt oxide, 0.5% nickel oxide, 1.5% tin oxide, and 5-15% multi-scale HNRP.
[0068] In another embodiment, when the substrate surface is a steel sheet and the applied coat is a ground coat, the frit composition includes 20.4% feldspar, 35.8% borax, 17.7% quartz, 5.3% soda ash, 4.5% sodium saltpeter, 4.9% fluorspar, 6.5% barium carbonate, 2.4% sodium silicofluoride, 0.5% cobalt oxide, 0.5% nickel oxide, 1.5% tin oxide, and 5-15% multi-scale HNRP.
[0069] In another embodiment, where the substrate surface is a steel sheet and the coating to be applied is a cover coat, the frit composition comprises a 0.8 mm thick cover coat, the frit comprising 22.8% feldspar, 23.1% borax, 21.1% quartz, 6.3% soda ash, 3% sodium saltpeter, 3.4% fluorspar, 10.1% cryolite, 6.8% sodium antimonate, and 3.4% zinc oxide, and 5-15% Multiscale HNRP.
[0070] The percentages of the frit components are merely examples and the actual frit composition will depend on the substrate surface and whether it is a ground coat or a cover coat.
[0071] The primary frit can be applied to the substrate surface (step 106) using dry or wet methods.
[0072] In the wet process, the primary frit is mixed with water to produce an aqueous suspension. Additional flotation agents, such as clay, are then added. The primary frit is then applied to the substrate surface by dipping or spraying. The application of the wet frit can be via dip coating, flow coating, spray coating, electrostatic wet spray coating, or electrophoretic coating. For example, in a wet process cast iron cover enamel coat, the frit mixture can be 23% feldspar, 24% borax, 12% quartz, 8% soda peter, 2% fluorite, 6% cryolite, 10% barium carbonate, 4% sodium silicofluoride, 6% zinc oxide, 10% boric acid, 8% antimony oxide, as well as multi-scale HRNP.
[0073] In the dry process, the frit is ground without water and then applied to the substrate surface, for example, via electrostatic dry powder. The frit is encapsulated with one or more organic compounds, such as organosilanes, such that the particles of the organic compounds are electrically charged and encapsulate the dry frit. In this manner, the frit can be "sprayed" onto the substrate surface, allowing electrostatic attachment to the substrate surface. For example, in a dry process cast iron cover enamel coat, the frit mixture can be 34.3% feldspar, 19.3% borax, 7.7% soda ash, 2.6% soda peter, 7.3% fluorite, 3.4% cryolite, 9.2% zinc oxide, 8.1% red lead, 8.1% tin oxide, as well as multi-scale HRNP.
[0074] The substrate surface is then subjected to a primary firing (step 108). The firing time and temperature depend on the type of substrate surface. Aluminum enamel is fired at 538-593°C for about 10 minutes. Dry cast iron is fired at 816-927°C for about 5 minutes. Wet cast iron is fired at 732-816°C for about 10-20 minutes. The ground coat of the thin steel plate is fired at 760-871°C for about 1-4 minutes.
[0075] Optionally, the primary fire (step 110) can be followed by an additional fire at a similar temperature and time, depending on the desired thickness and other properties.
[0076] A coating is then applied over the enamel covering the substrate surface (step 112). The coating can be one or more of a resin / epoxy coating or a clear coating. Other coatings can also be used.
[0077] After all coating applications are complete, the substrate surface is cured (step 114) to terminate the method. Curing is performed at a temperature of 230-250°C.
[0078] It should be noted that the firing temperatures of frits of embodiments of the present invention are well below the melting temperatures of the nanoparticles contained therein, for example, barium sulfate has a melting point of 1345° C., titanium dioxide has a melting point of 1855° C., and zirconium silicate has a melting point of 1540° C., all well below the firing temperatures of less than 1000° C. Furthermore, because the melting points of the nanoparticles are higher than the enamel coating, the resulting nanoparticle-impregnated vitreous enamel coating maintains the high reflectance and emissivity ratios of the nanoparticles.
[0079] An embodiment of the present invention includes the application of a coating of vitreous enamel impregnated with multiscale nanoparticles, including frits of a mixture of conventional frit materials and multiscale HRNPs.Additional thermochromic materials, such as vanadium dioxide, can be added.
[0080] Vitreous enamel coatings impregnated with the HRNPs of the present invention can be fired onto many substrates, including commonly used roofing and exterior wall materials, including metallic materials such as galvanized iron, zinc, tin, steel, copper, or aluminum, as well as other materials such as clay, terracotta, ceramic tile, brick, fiber cement, concrete, or stone, such as slate.
[0081] In other embodiments of the present invention, various techniques can be employed to improve the properties of the resulting vitreous enamel coating, including the use of high purity silica sand (99.5-99.9%) in the primary frit to optimize one or more of the optical reflectance and optical emissivity.
[0082] In another embodiment of the invention, the underlying vitreous enamel coating containing multi-scale nanoparticles is provided with an additional overlying protective coating that is transparent to the solar sky-window frequency band of solar radiation as defined in the Background section above.
[0083] Accordingly, it is to be understood that the embodiments of the invention described herein are merely illustrative of the application of the principles of the invention. Reference herein to details of illustrated embodiments is not intended to limit the scope of the claims, but rather to describe those features regarded as essential to the invention.
Claims
1. 1. A coating for application to roof and exterior wall surfaces to promote radiative cooling, comprising:
1. A coating comprising one or more highly reflective multi-scale nanoparticles, said coating being a vitreous enamel coating, said vitreous enamel coating comprising 2-40% of the one or more highly reflective multi-scale nanoparticles by total weight of said vitreous enamel coating.
2. The coating of claim 1 , wherein one or more of the roof surface and the exterior wall surface is a metallic material.
3. 3. The coating of claim 2, wherein the metallic material is selected from the group consisting of steel, galvanized iron, cast iron, aluminum, zinc, tin, copper, metal mixtures, and metallic coatings.
4. The coating of claim 1 , wherein one or more of the roof surface and the exterior wall surface is a metallic material.
5. 5. The coating of claim 4, wherein the non-metallic material is selected from the group consisting of clay, terracotta, ceramic tile, brick, fiber cement, concrete, stone, and mixtures of non-metallic materials.
6. The one or more multi-scale highly reflective nanoparticles are selected from the group consisting of barium sulfate (BaSO 4 2. The coating of claim 1 ,
7. 10. The coating of claim 1, wherein the one or more multi-scale highly reflective nanoparticles are hexagonal boron nitride (h-BN).
8. The coating of claim 1 , wherein the one or more multi-scale highly reflective nanoparticles are zirconium silicate.
9. The coating of claim 1 , wherein the one or more multi-scale highly reflective nanoparticles are titanium dioxide.
10. The one or more multi-scale highly reflective nanoparticles are selected from the group consisting of barium sulfate (BaSO 4 ), hexagonal boron nitride (h-BN), zirconium silicate (ZrSiO 4 ), and titanium dioxide (TiO 2 2. The coating of claim 1 ,
11. The one or more multi-scale highly reflective nanoparticles are selected from the group consisting of barium sulfate (BaSO 4 ), hexagonal boron nitride (h-BN), zirconium silicate (ZrSiO 4 ), titanium dioxide (TiO 2 ), calcium carbonate (CaCO 3 ), zinc sulfide (ZnS), silicon dioxide (SiO 2 ), magnesium oxide (MgO), yttrium orthoaluminate (Al 5 O 12 Y 3 ), calcium oxide (CaO), magnesium aluminate (Al 2 MgO 4 ), and lanthanum aluminate (LaAlO 3 10. The coating of claim 1, wherein the coating is one or more of:
12. 10. The coating of claim 1, wherein the one or more multi-scale highly reflective nanoparticles of the coating increase reflectivity over a range of solar radiation from infrared to ultraviolet.
13. 10. The coating of claim 1, further comprising high purity silica sand, said high purity silica sand improving one or more of emissivity or reflectance of said coating.
14. 10. The coating of claim 1, wherein the one or more multi-scale highly reflective nanoparticles have a distribution of nanoparticles between 10 and 900 nm.
15. The coating of claim 1 , wherein the coating is an undercoat.
16. 10. The coating of claim 1, wherein the firing temperature of the vitreous enamel coating is less than the melting point of the one or more highly reflective multi-scale nanoparticles.
17. The one or more multi-scale highly reflective nanoparticles are selected from the group consisting of barium sulfate (BaSO 4 2. The coating of claim 1, wherein said first and second crystalline silicon nitrides are hexagonal boron nitride (h-BN).
18. The coating is made of vanadium dioxide (VO 2 10. The coating of claim 1 further comprising a thermochromic material of
19. The coating of claim 1 , wherein the coating is a covercoat.
20. The coating of claim 1 , wherein the coating is a primary coating.
21. 1. A method for applying a vitreous enamel coating to a roof and / or exterior wall substrate surface, comprising: determining the type of coating to be applied and the thickness of said coating; preparing a primary frit comprising one or more highly reflective multi-scale nanoparticles, said primary frit comprising 2-40% of the total weight of said vitreous enamel coating to be applied; applying the primary frit to the substrate surface using a wet or dry method; applying a first coating to the substrate surface by firing the applied primary frit at least once at a temperature below the melting point of the one or more multi-scale highly reflective nanoparticles; applying a second coating over the first coating; and curing the first coating and the second coating on the substrate surface.
22. 22. The method of claim 21, wherein the substrate surface is prepared to receive the first coating prior to forming the frit.
23. The method of claim 21 , wherein the first coating is a primary coating.
24. 22. The method of claim 21, wherein the first coating is an undercoat.
25. 22. The method of claim 21 , wherein the second coating is a clear coating.